Gene flow among populations of two rare co-occurring fern species differing in ploidy level - Bucharová, Anna; Münzbergová, Zuzana (PloS one, 2012)
Differences in ploidy levels among different fern species have a vast influence on their mating system, their colonization ability and on the gene flow among populations. Differences in the colonization abilities of species with different ploidy levels are well known: tetraploids, in contrast to diploids, are able to undergo intra-gametophytic selfing. Because fertilization is a post-dispersal process in ferns, selfing results in better colonization abilities in tetraploids because of single spore colonization. Considerably less is known about the gene flow among populations of different ploidy levels. The present study examines two rare fern species that differ in ploidy. While it has already been confirmed that tetraploid species are better at colonizing, the present study focuses on the gene flow among existing populations. We analyzed the genetic structure of a set of populations in a 10×10 km study region using isoenzymes. Genetic variation in tetraploid species is distributed mainly among populations; the genetic distance between populations is correlated with the geographical distance, and larger populations host more genetic diversity than smaller populations. In the diploid species, most variability is partitioned within populations; the genetic distance is not related to geographic distance, and the genetic diversity of populations is not related to the population size. This suggests that in tetraploid species, which undergo selfing, gene flow is limited. In contrast, in the diploid species, which experience outcrossing, gene flow is extensive and the whole system behaves as one large population. Our results suggest that in ferns, the ability to colonize new habitats and the gene flow among existing populations are affected by the mating system.
Keywords: tok genů; heterozygot; rozmnožování; Ploidies; Gene Flow; Ferns; Reproduction; Plant Proteins; Heterozygote; inbreeding; ploidie; rostlinné proteiny; Genetic Variation; rostlinné geny; kapradiny; alely; Inbreeding; Alleles; Isoenzymes; genetické markery; genetická variace; Genes, Plant; izoenzymy; Genetic Markers